EFFECT OF DOMESTIC POULTRY FARM TO COMMERCIAL POULTRY FARMS TO INCREASE RISK OF INFLUENZA TO SOCIETY - Thomson, Pro. Maidhura; Smith, Dr. Grey (International Journal of Multidisciplinary Research and Studies, 2021)
This paper summarizes the evidence that the contribution of backyard poultry flocks to the continued transmission dynamics of an avian influenza epidemic in commercial flocks is modest at the best. Nevertheless, while disease control strategies needn’t involve the backyard flocks, an analysis of the contribution of every element of the subsequent generation matrix to the essential reproduction number indicates that models which ignore the contribution of backyard flocks in estimating the hassle required of strategies focused on one host type (e.g. commercial flocks only) necessarily underestimate the amount of effort to an extent that will interest policymaker.